An intelligent system using adaptive wavelet entropy for automatic analog modulation identification - Avci, D. (Academic Press Inc Elsevier Science, 2010)
In this paper, an intelligent analog modulation identification system is presented for interpretation of the analog modulated signals. This paper especially deals with combination of the feature extraction and classification for analog modulated signals. The analog modulated signals used in this study are six types (AM, DSB, USB, LSB, FM, and PM). Here, a discrete wavelet neural network-adaptive wavelet entropy (DWNN-ANE) model is used, which consists of two layers: discrete wavelet-adaptive wavelet entropy and multi-layer perceptron neural networks for intelligent analog modulation identification. The discrete wavelet layer is used for adaptive feature extraction in the time-frequency domain and is composed of DWT and adaptive wavelet entropy. The performance of the used system is evaluated by using total 1080 analog modulated signals. These test results show the effectiveness of the used intelligent system presented in this paper. The rate of correct classification is about 98.34% for the sample analog modulated signals. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Discrete wavelet transform; Wavelet neural network system; Intelligent analog modulation identification; Analog modulated signal; Feature extraction; Wavelet entropy; Intelligent system